Modified Crosstalk between Phytohormones in Arabidopsis Mutants for PEP-Associated Proteins - Bychkov, Ivan A; Andreeva, Aleksandra A; Vankova, Radomira; Lacek, Jozef; Kudryakova, Natalia V; Kusnetsov, Victor V (International journal of molecular sciences, 2024)
Plastid-encoded RNA polymerase (PEP) forms a multisubunit complex in operating chloroplasts, where PEP subunits and a sigma factor are tightly associated with 12 additional nuclear-encoded proteins. Mutants with disrupted genes encoding PEP-associated proteins (PAPs) provide unique tools for deciphering mutual relationships among phytohormones. A block of chloroplast biogenesis in Arabidopsis pap mutants specifying highly altered metabolism in white tissues induced dramatic fluctuations in the content of major phytohormones and their metabolic genes, whereas hormone signaling circuits mostly remained functional. Reprogramming of the expression of biosynthetic and metabolic genes contributed to a greatly increased content of salicylic acid (SA) and a concomitant decrease in 1-aminocyclopropane-1-carboxylic acid (ACC) and oxophytodienoic acid (OPDA), precursors of ethylene and jasmonic acid, respectively, in parallel to reduced levels of abscisic acid (ABA). The lack of differences in the free levels of indole-3-acetic acid (IAA) between the pap mutants and wild-type plants was accompanied by fluctuations in the contents of IAA precursors and conjugated forms as well as multilayered changes in the expression of IAA metabolic genes. Along with cytokinin (CK) overproduction, all of these compensatory changes aim to balance plant growth and defense systems to ensure viability under highly modulated conditions.
Keywords: plastidy; proteiny huseníčku; regulace genové exprese u rostlin; Arabidopsis thaliana; gene expression; phytohormones; PEP-associated proteins; regulátory růstu rostlin; mutants; Arabidopsis Proteins; Chloroplasts; Plant Growth Regulators; Gene Expression Regulation, Plant; Plastids; Arabidopsis; chloroplasty